Chopper-Stabilized Instrumentation Amplifier with Automatic Frequency Tuning Loop - Wu, Chen-Mao; Chen, Hsiao-Chin; Yen, Ming-Yu; Yang, San-Ching (Micromachines (Basel), 2018)
A variable-gain chopper-stabilized instrumentation amplifier (chopper IA), which employs a low pass filter (LPF) to attenuate the up-converted noise at the chopping frequency, is presented. The circuit is designed and fabricated with Taiwan Semiconductor Manufacturing Company (TSMC) (Hsinchu, Taiwan) 0.18 μm complementary metal-oxide-semiconductor (CMOS) technology. Consuming 1.1 mW from a 1.2 V supply voltage, the chopper IA achieves a variable gain of 20.7–48.5 dB, with a minimum bandwidth of 6.7 kHz and a common-mode rejection ratio (CMRR) of 95 dB below 10 kHz. By using the chopper technique, the input-referred noise of the chopper IA can be reduced to 0.28 μVrms (0~96 kHz), with a chopping frequency of 83.3 kHz. An automatic frequency tuning loop (ATL) is employed to adjust the corner frequency of the LPF dynamically so that the frequency ratio between the chopping frequency and the LPF corner frequency is 8.3, ensuring a noise reduction of 36.7 dB.